Pengaruh Kualitas Pelayanan dan Keberagaman Produk Terhadap Loyalitas Pelanggan di Toko Emas Berkah Arifin 2 Kota Blitar - Mella Sukma Setiawan; Ayu Sulasari; Joko Samboro (Indo Publishing, 2025)
The dynamic development of the global economy has contributed to business growth in developing countries, including Indonesia, particulary in the fashion sector. Gold jewelry is one of the most in-demand fashion items, especially among women. Toko Emas Berkah Arifin 2 in Blitar city is known for its quality service and diverse product offerings. This study aims to examine the effect of service quality and product diversity on customer loyalty at Toko Berkah Arifin 2 in Blitar city. This research was quantitative, involving three variables service quality, product diversity, and customer loyalty. The study used observation and questionnaires for data collection, and through purposive sampling, obtained 97 respondents who were customers of Toko Emas Berkah Arifin 2 in Blitar City. Data analysis was conducted with multiple linear regression, using SPSS 26 for Windows. The hypothesis testing results showed that both partially and simultaneously, service quality and product diversity had a positive and significant impact on customer loyalty. Service quality contributed more strongly than product diversity, indicating that customers were more loyal to stores offering consistent, responsive, and expectation-aligned service.Based on the results of this study, it can be concluded that enhancing service quality and product diversity is essential for building customer loyalty at Toko Emas Berkah Arifin 2 Blitar City. Providing excellent service and offering a wide range of products contribute to customer comfort and satisfaction, thereby strengthening loyalty in competitive market.